Cover Image, Volume 69, Issue 4. Issue 4 (6th March 2020) - Jin, Chenhao; Leng, Xuefei; Zhang, Manwen; Wang, Yanshai; Wei, Zhiyong; Li, Yang
Abstract: The cover image is based on the Research Article Fully biobased biodegradable poly(l‐lactide)‐b‐poly(ethylene brassylate)‐b‐poly(l‐lactide) triblock copolymers: Synthesis and investigation of relationship between crystallization morphology and thermal properties by Chenhao Jin et al., https://doi.org/10.1002/pi.5958 . Abstract : The cover image is based on the Research Article Fully biobased biodegradable poly(l‐lactide)‐b‐poly(ethylene brassylate)‐b‐poly(l‐lactide) triblock copolymers: Synthesis and investigation of relationship between crystallization morphology and thermal properties by Chenhao Jin et al., https://doi.org/10.1002/pi.5958 .